The EEC/EU as an Evolving Compromise between French Dirigism and German Ordoliberalism (1957–1995). (18th January 2019) - Warlouzet, Laurent
Abstract: This contribution explores the origins of the mutation of the concept of the 'social market economy', from its ordoliberal roots, to its contemporary broader meaning, by examining to what extent it was influenced by the perennial debate between French dirigism and German ordoliberalism. After an initial section defining both concepts, the contribution proceeds to unearth long‐forgotten conflicts between both approaches from the 1960s to the 1980s on European planning, on industrial policy and on competition policy. A final section delves into the Delors synthesis and the EMU compromise.